Analysis of rural environmental quality in Glagah Subdistrict, Lamongan Regency, East Java - Eko Sutrisno; Mulono Apriyanto; Sri Ndaru Arthawati; Apriningsih Apriningsih; Lilla Puji Lestari (Research and Social Study Institute, 2023)
There are several types of environmental pollution in rural areas in Glagah Subdistrict, Lamongan Regency, such as water, soil, and air pollution. Air pollution occurs because the Glagah Subdistrict is crossed by the inter-regency axis road, which is travelled by many vehicles. Meanwhile, water and soil pollution in this area occur due to fish farming and ponds. In addition, Glagah Subdistrict in Lamongan Regency is considered a flood-prone area due to high rainfall that causes the overflow of Bengawan Solo River. This study aims to determine the quality of the rural environment in Glagah Subdistrict. This study used survey and questionnaire methods. Data were analyzed quantitatively using statistical calculations and frequency tables supported by descriptive analysis. The research parameters observed were environmental quality, disaster-prone potential, and the existence of disaster response by the local village government. The results of this study show that villages in Glagah Subdistrict do not experience air or soil pollution, as they are located far from industrial areas. Instead, water pollution occurs every year, characterized by the proliferation of water hyacinth that covers the surface of the rivers, thus inhibiting the flow of river water. Potential disasters in Glagah Subdistrict are flooding and tornado. Flooding occurs in seven villages located near Bengawan Jero (a tributary of Bengawan Solo) and can be categorized as annual flooding. Villages that are annually affected by flooding do not have disaster mitigation plans, even though funds for such activities are available. Therefore, cross-sectoral cooperation is needed to overcome the annual flooding in Glagah Subdistrict.